2018
DOI: 10.1111/1440-1681.12967
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid‐alcohol crosstalk: Recent advances on a bi‐faceted target

Abstract: Increasing evidence has focusesed on the endocannabinoid system as a relevant player in the induction of aberrant synaptic plasticity and related addictive phenotype following chronic excessive alcohol drinking. In addition, the endocannabinoid system is implicated in the pathogenesis of alcoholic liver disease. Interestingly, whereas the involvement of CB receptors in alcohol rewarding properties is established, the central and peripheral action of CB signalling is still to be elucidated. This review aims at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 106 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…However, studies also showed the involvement of the ECS in addictive behavior ( 104 , 105 ) and the association of early childhood and adolescent exposure to cannabinoids with addictive behavior ( 91 , 106 ). There are still gaps in our understanding, but the discovery of the expression of CB2Rs in brain regions involved in drug addiction, such as the ventral tegmental area (VTA), nucleus accumbens (NAc), amygdala and hippocampus unraveled and encouraged investigation of the role of CB2Rs and their potential therapeutic target in drug addiction ( 107 , 108 ). Pharmacologic and genetic studies showed that CB2Rs are involved in the effects of psychostimulants like cocaine, amphetamine and methamphetamine.…”
Section: Cannabinoid Type 2 Receptors In Neuropsychiatric and Neurode...mentioning
confidence: 99%
“…However, studies also showed the involvement of the ECS in addictive behavior ( 104 , 105 ) and the association of early childhood and adolescent exposure to cannabinoids with addictive behavior ( 91 , 106 ). There are still gaps in our understanding, but the discovery of the expression of CB2Rs in brain regions involved in drug addiction, such as the ventral tegmental area (VTA), nucleus accumbens (NAc), amygdala and hippocampus unraveled and encouraged investigation of the role of CB2Rs and their potential therapeutic target in drug addiction ( 107 , 108 ). Pharmacologic and genetic studies showed that CB2Rs are involved in the effects of psychostimulants like cocaine, amphetamine and methamphetamine.…”
Section: Cannabinoid Type 2 Receptors In Neuropsychiatric and Neurode...mentioning
confidence: 99%
“… 9 , 28 Consequently, the endocannabinoid system and its receptors were found to be involved in the pathophysiological mechanisms of ALD by regulating immune function, metabolic modulation, and inflammatory response in the onset and progression of ALD. 29 , 32 Because the expression of CB1R and CB2R is well identified in hepatocytes and various nonparenchymal cells in the liver, accurate comprehension of the regulatory mechanisms by which alcohol exposure generates or stimulates the production of endocannabinoids—as well as the effects of alcohol on the activation of cannabinoid receptors—could lead to a breakthrough in understanding the exact pathophysiology of ALD and in discovering potential therapeutic targets.…”
Section: Cannabinoid Signaling In the Pathogenesis Of Aldmentioning
confidence: 99%
“…To date, it is known that CB1R activation aggravates inflammation, steatosis, and fibrosis through the reduction of fatty acid oxidation and TG-VLDL secretion, enhanced de novo lipogenesis, and activation of HSCs, whereas CB2R inhibits inflammation and steatosis and has anti-fibrotic properties by exerting anti-inflammatory functions on Kupffer cells. 29 , 32 Figure 3 summarizes the opposite roles of CB1R and CB2R in the progression of ALD.…”
Section: Cannabinoid Signaling In the Pathogenesis Of Aldmentioning
confidence: 99%
“…The CB1 receptors were found to promote the progression of fibrosis as CB1 antagonism was able to attenuate liver fibrogenesis primarily by decreasing hepatic TGF-β [121]. CB1 and CB2 receptors have also been shown to play opposite roles in the pathogenesis of alcoholic liver disease via regulation of reinforcing properties of alcohol in the brain as well as hepatic cell injury and inflammation by endocannabinoids [122].…”
Section: Prenatal Cannabinoid Exposure and Immune Dysregulationmentioning
confidence: 99%